Labor Politics and the Return of Neoliberalism in Argentina - Elbert, Rodolfo Gaston (2016)
On November 22nd, 2015, Argentines elected Mauricio Macri as President for the 2015-2019 term, by a margin of less than three percent. Macri s defeat of the Peronista candidate Daniel Scioli marked the end of the long Kirchnerista decade, 2003-2015: after a period of increasing state intervention in the economy and limited wealth redistribution, a center-right candidate with an anti-corruption discourse now leads Argentina. This article explore the reasons for this triumph and the challenges that the labor movement faces after this political change